2019
DOI: 10.1091/mbc.e19-01-0009
|View full text |Cite
|
Sign up to set email alerts
|

An actin-based protrusion originating from a podosome-enriched region initiates macrophage fusion

Abstract: Macrophage fusion resulting in the formation of multinucleated giant cells occurs in a variety of chronic inflammatory diseases, yet the mechanism responsible for initiating this process is unknown. Here, we used live cell imaging to show that actin-based protrusions at the leading edge initiate macrophage fusion. Phase-contrast video microscopy demonstrated that in the majority of events, short protrusions (∼3 µm) between two closely apposed cells initiated fusion, but occasionally we observed long protrusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…Since PTFE plastic is not amenable to most imaging techniques, we took advantage of recently developed optical-quality glass surfaces prepared by adsorption of longchain hydrocarbons such as paraffin that promote high level of macrophage fusion (Faust et al, 2017;Faust et al, 2018). In this series of experiments, rather than macrophage cell lines, we used primary macrophages isolated from inflamed mouse peritonea (Helming and Gordon, 2007a;Podolnikova et al, 2016;Faust et al, 2019) to avoid the robust proliferation observed in the cultures of macrophage cell lines. Using phase-contrast video microscopy, we determined that the kinetics of IL-4-induced macrophage fusion on paraffin-adsorbed glass (P-surface) were similar to that on PCTFE ( Figure 2A and B).…”
Section: Formation Of Zlss In Vitromentioning
confidence: 99%
See 4 more Smart Citations
“…Since PTFE plastic is not amenable to most imaging techniques, we took advantage of recently developed optical-quality glass surfaces prepared by adsorption of longchain hydrocarbons such as paraffin that promote high level of macrophage fusion (Faust et al, 2017;Faust et al, 2018). In this series of experiments, rather than macrophage cell lines, we used primary macrophages isolated from inflamed mouse peritonea (Helming and Gordon, 2007a;Podolnikova et al, 2016;Faust et al, 2019) to avoid the robust proliferation observed in the cultures of macrophage cell lines. Using phase-contrast video microscopy, we determined that the kinetics of IL-4-induced macrophage fusion on paraffin-adsorbed glass (P-surface) were similar to that on PCTFE ( Figure 2A and B).…”
Section: Formation Of Zlss In Vitromentioning
confidence: 99%
“…It is known that the Arp2/3 complex and its activators Cdc42 and WASp nucleate the core of actin filaments in podosomes (Linder et al, 2000). We have previously demonstrated that deficiency of WASp or Cdc42, or inhibition of Arp2/3 strongly reduces macrophage fusion and podosome formation (Faust et al, 2019). To examine the importance of these actin regulators in ZLS formation, we isolated macrophages form WASP -/or myeloid-cell-specific Cdc42 -/mice and tested their ability to assemble ZLSs.…”
Section: Zlss Contain Proteins Found In Podosomesmentioning
confidence: 99%
See 3 more Smart Citations